Hubungan Islam dan Yahudi Nasrani dalam Prespektif Hadis - Uccok Kurnia Meliala Hasibuan; Fitriani (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2024)
The purpose of this study is to find out Jewish history in a hadith view. In the Bible account, this marks the beginning of Abraham's journey to what is now Can'an, Palestine. The prophet Ya'qub and his sons, who later left Canaan for Egypt, are mentioned in the early history of the Jews, also known as the Children of Israel, in the Qur'an and Hadith. The research methodology used in this study is a qualitative descriptive approach. The research resources used in this procedure come from books, magazines, literature, journals, theses, and primary and secondary data sources. Literary methodology is a method used to obtain data. To draw conclusions from all the research findings, data reduction is the data analysis approach used in this study.the results of the study show that: 1) In history, other names of Jews used throughout history have been Hebrew, Bani Israel, Jew, and Zionist. Nonetheless, there was a difference of opinion about the term "Jew" itself until the author realized that it appeared after the death of Moses (a.s.). 2) The Old Testament, the Talmud, and the Protocol of Zionist Philosophy are scriptures that serve as guides. The Jews also split into a number of factions throughout their history, including the Samiritans, Al-Muqarabah and al-Yuz'aniyyah, the Pharisees, the Essenes, the Inanids, the Muta'assibun, and a few more. 3) The Jews continued to fight against each other until the Zionist movement, which is more widely known today to fight for a tahah that was not their right.